A New Soil-Based Solution for Reducing the Persistence of Parasites in Zoos - José Ángel Hernández; Cándido Viña; João Lozano; Izaro Zubiría; Miguel Baena; Inês Abreu-Ramos; Rami Salmo; Esther Valderrábano; Gustavo Pérez-Anzúrez; Adolfo Paz-Silva; Rodrigo Muíño; Cristiana Cazapal-Monteiro; et al. (Journal of Zoological and Botanical Gardens)
Controlling parasites in zoo animals is a significant challenge, making practical infection prevention methods essential. This study evaluated a novel solution using parasitophagous fungi-treated forage seeds to reduce soil parasite persistence. We conducted two experiments to assess the soil distribution of the fungi Mucor circinelloides (ovicidal) and Duddingtonia flagrans (larvicidal). Forage seeds were immersed in a submerged culture containing 106 spores/mL and subsequently sown in plastic trays (trial 1) and demarcated ground plots (40 × 30 cm) framed with wood (trial 2). Fifteen days later, Ascaris suum and cyathostomin eggs were placed above the germinated vegetation. After a 25–30-day period, the viability of roundworm eggs reduced by 62%, and half of them remained undeveloped; a 64% reduction in the counts of L3 cyathostomins was recorded. In trial 2, viability decreased by 55% in roundworm eggs, with an infectivity rate of 30%, while L3 counts lessened by 57%. It has been concluded that the risk of infection by ascarids and cyathostomins can be reduced by at least half by sowing the soil with forage seeds pre-treated with fungi, providing a practical solution for parasite control in zoos.